2012
DOI: 10.1182/blood-2011-09-377853
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic N-cadherin is not required for microenvironmental support and regulation of hematopoietic stem and progenitor cells

Abstract: Hematopoietic stem cell (HSC) regulation is highly dependent on interactions with the marrow microenvironment. Controversy exists on N-cadherin's role in support of HSCs. Specifically, it is unknown whether microenvironmental N-cadherin is required for normal marrow microarchitecture and for hematopoiesis. To determine whether osteoblastic N-cadherin is required for HSC regulation, we used a genetic murine model in which deletion of IntroductionThe molecular signals that mediate regulatory microenvironmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 39 publications
4
67
2
Order By: Relevance
“…A number of studies have demonstrated a direct relationship between osteoclast activity and bone remodeling and an increase in connectivity density. 33,34 Importantly, and as expected, the connectivity density (Conn D) was slightly higher in the group with osteoclasts (Fig. 3B).…”
Section: Fig 2 Characterization Of Osteoclasts Within a Tissue-engisupporting
confidence: 85%
“…A number of studies have demonstrated a direct relationship between osteoclast activity and bone remodeling and an increase in connectivity density. 33,34 Importantly, and as expected, the connectivity density (Conn D) was slightly higher in the group with osteoclasts (Fig. 3B).…”
Section: Fig 2 Characterization Of Osteoclasts Within a Tissue-engisupporting
confidence: 85%
“…9,78,79 Notably, activation of the PTH receptor solely in osteocytes is not sufficient to expand HSPCs, suggesting differential effects of PTH on osteolineage cells depending on maturation stages. 9,80 The ability of PTH (1-34) to promote HSPC support and maintenance is likely the result of its stimulatory effect on various cell types in the marrow, including osteolineage cells and, indirectly, osteoclasts and even macrophages.…”
Section: Hormonal Signalsmentioning
confidence: 99%
“…In the HSC niche, HSCs and osteoblasts express N-cadherin (Zhang et al, 2003), and multiple studies have suggested that N-cadherin is required for maintaining HSCs in the niche for long-term self-renewal (Haug et al, 2008;Hosokawa et al, 2010a;Hosokawa et al, 2010b). However, other independent studies have disputed the role of Ncadherin in controlling HSC self-renewal (Bromberg et al, 2012;Greenbaum et al, 2012;Kiel et al, 2009). The contradictory conclusions concerning the role of N-cadherin in the regulation of HSC self-renewal could arise from different experimental methods.…”
mentioning
confidence: 99%